2021
DOI: 10.1016/j.cmi.2020.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in patients hospitalized for COVID-19 pneumonia who require oxygen: observational comparative study using routine care data

Abstract: Objective To assess the effectiveness of corticosteroids on outcomes of patients with COVID-19 pneumonia requiring oxygen without mechanical ventilation. Methods We used routine care data from 51 hospitals in France and Luxembourg to assess the effectiveness of corticosteroids at 0.8 mg/kg/day eq. prednisone (CTC group) versus standard of care (no-CTC group) among adults 18 to 80 years old with confirmed COVID-19 pneumonia requiring oxygen without mechanical ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…Indeed, in our cohort, patients without inflammation had less severe pneumonia symptoms ( S5 Table ). Our results are consistent with those of other studies which also found that steroids were beneficial in the subgroup of patients with inflammation [ 15 , 19 , 39 ]. Another observational study reported similar results but also a deleterious effect of CS for patients with a C-Reactive protein below 10 mg/dL [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, in our cohort, patients without inflammation had less severe pneumonia symptoms ( S5 Table ). Our results are consistent with those of other studies which also found that steroids were beneficial in the subgroup of patients with inflammation [ 15 , 19 , 39 ]. Another observational study reported similar results but also a deleterious effect of CS for patients with a C-Reactive protein below 10 mg/dL [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…The subsequent MEtCOVID trial did not show a difference in mortality at day 28 between treatment groups [15] but suggested a benefit of CS in patients aged over 60. Finally, several observational studies yielded conflicting results [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal timing of corticosteroid prescription is still controversial, and the indication "in patients requiring oxygen" may be ambiguous. However, an exciting report trying to clarify the timely medication found that only the patients requiring ≥ 3 L/min and CRP ≥ 100 mg/L who received corticosteroids had less risk of death or intubation [9]. This finding suggests a rationale for corticosteroid prescription based on a combination of oxygen supplementation with inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Dans celle-ci, aucune association n'a été retrouvée entre l'utilisation de corticostéroïdes et l'intubation ou le décès dans la population de patients âgés de 18 à 80 ans hospitalisés dans des unités de soins non intensifs. Cependant, le traitement a été associé à une réduction du risque d'intubation ou de décès dans le sous-groupe des patients avec ≥ 3 L/min d'oxygène, ou avec un taux de protéine C-réactive (CRP) ≥ 100 mg/L [22] .…”
Section: Prise En Charge Hospitalière Des Formes Sévères Et Critiquesunclassified